Moraxella occupied the largest proportion in the nasal microbiome in healthy children, which potential protect them from COVID-19. (September 2022) - Yu, Xia; Wang, Li; Zheng, XueMei; Wen, Yizhou; Zhang, Zhirong; Fan, Lingxia; Zhou, Qin; Yang, Xiao; Xue, Binqian; Lin, Yonghong
Abstract: Background: In the prevalence of COVID-19, infection symptoms are different in children and adults. In this study to investigate the differences in the upper respiratory tract microbiome profile between healthy children and adults and to explore which microbiome protect them from COVID-19. Methods: Thirty healthy children and 24 healthy adults were enrolled between October 2020 and January 2021. Nasal and throat swabs were obtained at enrollment, and DNA was extracted. We performed 16S rDNA sequencing to compare the alpha and beta diversity of the nasal and throat microbiomes between children and adults and assessed potential microbiome biomarkers. Results: In the nasal microbiome, there were significant differences between healthy children and adults, and Moraxella occupied the largest proportion in healthy children. Notably, there was no significant difference between healthy children and adults in the throat microbiome, and it was predominated by Firmicutes. In the function analysis, compared with adults, there was increased enrichment in pathways related to amino acid metabolism and lipid metabolism, in children. Conclusions: In the upper respiratory tract microbiome profiles, Moraxella may be involved in protecting children from COVID-19 infections and may be involved the amino acid metabolism and lipid metabolism. Highlights: Moraxella made up the largest proportion of the nasal microbiome in healthy children. Moraxella may be involved in protecting children from COVID-19 infection in the upper respiratory microbiome. Amino acid metabolism and lipid metabolism may be involved in the protective role of Moraxella.